Mujeres en la murga porteña: Arte, territorialidad y empoderamiento - Almendra Aladro (Les Cahiers ALHIM)
The objective of this article was to analyze the murga porteña phenomenon from a double perspective that questions both gender relations and the Right to the City, understood as a macro-legal theoretical construction that puts access and enjoyment of rights in crisis in the capitalist urban context. In order to achieve this purpose, we have carried out a bibliographic analysis that allows us to account for the complexity of the object we address and the importance of mainstreaming the proposed analysis perspectives. Finally, we decided to interview one of the founders of the murga "Los Colgados de Nueva Pompeya" of the city of Mar del Plata with the aim of investigating the peculiarities that women members of the local murguera groups are going through. The work realized reflects that the progressive incorporation of women into this genre has produced its artistic resignification and has turned it into a tool of struggle for political participation in the management of urban rights and, in particular, of the cultural type. Despite the advance of the feminist movement in Argentina, through visualization phenomena such as #NiUnaMenos, the truth is that functions such as direction and percussion into the murgas are still resisted from the masculine hegemony and represents an interesting challenge.